Atypical antipsychotics-induced metabolic syndrome and nonalcoholic fatty liver disease: a critical review - Xu, Haiyun (Neuropsychiatr Dis Treat, 2019)
The atypical antipsychotics (AAPs) have been used as first-line drugs in psychiatric practice for a wide range of psychotic disorders, including schizophrenia and bipolar mania. While effectively exerting therapeutic effects on positive and negative symptoms, as well as cognitive impairments in schizophrenia patients, these drugs are less likely to induce extrapyramidal symptoms compared to typical antipsychotics. However, the increasing application of them has raised questions on their tolerability and adverse effects over the endocrine, metabolic, and cardiovascular axes. Specifically, AAPs are associated to different extents, with weight gain, metabolic syndrome (MetS), and nonalcoholic fatty liver disease (NAFLD). This article summarized clinical evidence showing the metabolic side effects of AAPs in patients with schizophrenia, and experimental evidence of AAPs-induced metabolic side effects observed in animals and cell culture studies. In addition, it discussed potential mechanisms involved in the APPs-induced MetS and NAFLD.